PEMANFAATAN ANIMASI NUSSA DAN RARA SEBAGAI MEDIA PEMBINAAN KARAKTER ANAK DI DESA LAMDINGIN BANDA - Hamdi Yusliani hamdiyusliani; Rosnidarwati Rosnidarwati (LPPM Universitas Al Muslim, 2021)
Technology is one of the fastest growing media today. An important thing is how to use a variety of technology media to become a part of educational media. The children most favored media as students are television, laptop and cellphone/smartphone. However, it is undeniable that there are many shows available on these media, which are not entirely good for children to be watched. One of the animated films that can give a good moral message and a lot of Islamic education is the Nussa and Rara series. This community service is carried out as one of the strategies to make Nussa and Rara animation shows as an educational spectacle in growing children's Islamic characters for children and motivating children to be smart in selecting shows from the internet. This activity takes children in Gampong Lamdingin, Kuta Alam District, Banda Aceh. The service period used was 2 days with several series of activities, namely an assessment of children's behavior through observation and interviews, counseling on character education for children, watching together the Nussa and Rara series, competitions/quizzes and distribution of prizes and souvenirs. The result of this service is an increase in knowledge and understanding of these school-aged children about noble character values and to motivate them to be smarter in selecting good and more educational shows.